The role of peace & diplomacy in the arctic geopolitical & military shift originated by arctic maritime-related industries - Viguier, Thomas Georges Raymond, 1992- (2021)
Verkefnið er lokað til 01.04.2050. After Cold War, the Arctic progressively scale down in terms of geopolitics and military contingency as the United States of America and the Russian Federation (which replaced the Soviet Union) were no longer in a Cold War in the Arctic. As both countries operated a shift from a hard conception of realism towards liberalism due to the large expenses the Cold War generated, conflicts shifted to other regions, such as the Middle East. However, the diminution in sea ice during the past decade has made possible the exploitation of Arctic resources and the Northern Sea Route, causing a geopolitical and military regain in the region. The recent events involving Greenland and the increase in military capacity in the Russian Arctic have made evident the major military and geopolitical stakeholders in the region: Russia, the United States of America, and China. As the Arctic holds some of the remaining untapped resources in the World and represents the opportunity for the shipping industry to exploit new and cheaper maritime routes than the traditional ones, all stakeholders are trying to gain as much control as possible over the Arctic maritime areas and operations. In this sense, Arctic and non-Arctic States with interests in the Arctic are developing policies and technologies that target the assertion of strategic, sovereign and economic claims in the Arctic region. Despite the fact that these States are achieving realist policies that may increase military tensions in the region, peace and diplomacy may play a crucial role in maintaining a long-term stability that would benefit to all stakeholders and avoid another Cold War in the Arctic. Therefore, an analysis of peace theories and diplomatic approaches for the Arctic may help in understanding local circumstance and how the current trend are influencing Arctic affairs, taking maritime-related industries as a common ground for the analysis.